"Formulating a New Healthcare System with Old Ideals: America's Next Step". Issue 1 (2nd January 2020) - Wolek, Matthew R.; Spinelli, Robert J.
Abstract: The American healthcare system is in chaos. It is in shambles because of what American's value and how they have changed over time. American values have changed with their healthcare system. To help adopt a single-payer system, Americans and their government need to see how their values can coexist with that system. Americans can become open to the idea by making a new system that appeals to what they value. The current healthcare system does not cover everyone, costs more than, and produces lower health outcomes compared to the rest of the developed world. If the American healthcare system is to adopt a single payer system, they would need to shape it around what they value as a nation.